The Effect of Adding POC (Liquid Organic Fertilizer) With Different Dosage in Maintenance Media on the Growth of Gurame Fish (Osphronemus gouramy ) In Aquaponic System - Nurul Syafika; Rusliadi Rusliadi; Mulyadi Mulyadi; Niken Ayu Pamukas; Heri Masjudi; Novreta Ersyi Darfia (Jurnal Akuakultur SEBATIN, 2022)
The research it was conducted on March to May 2021 at Hatchery Faculty of Fisheries and Marine, University of Riau. This study aims to determine the growth of Osphronemus gouramy fish that given POC (Organic Liquid Fertilizer) with different doses with the Aquaponic system. This research using a container bucket -sized 100 liters as much as 15 units. Dose POC ( Fertilizer Organic Liquid ) were used in the study is that P 0 (control), P 1 (0.5 ml / l), P 2 (0.875 ml / l), P 3 (1.25 ml / l), P 4 (1.625 ml / l), the technology that is used in research this is a technology Aquaponics to use the swamp as a plant . The method that is used in research is a method of experimentation that is Design Randomized Complete (RAL) one factor with a five- stage treatment and three times repetition . From the results of the research that has been done it can be known that the treatment that is best in research is the treatment of P 3 , namely the provision of POC ( Fertilizer Organic Liquid ) with a dose of 1.25 ml / l. Water quality during the study obtained temperature 26.0-26.6°C, pH 6.20-7.98, DO 6.1-7.9 mg/l, ammonia 0.0002-0.0014 mg/l, and bundance of phytoplankton 112.319 ind/l. Giving a dose of POC ( Fertilizer Organic Liquid ) differ in the maintenance of fish carp give the effect that the real against the growing weight of absolute of 10.20 grams, the growth of long- absolute of 4.26 cm, the rate of growth specifically by 1.91%, the conversion of feed at 0, 93%, 100% survival rate , plant absolute weight 7.26 grams, and plant absolute length 37.33 cm.